The correlation of slip transmission/blockage with the fracture in Al-Mg alloy. (June 2023) - Zong, S.W.; You, X.J.; Yang, J.; Dan, C.Y.; Jin, L.; Shi, Q.W.; Wang, H.W.; Chen, Z.
Abstract: An in-situ tensile test of Al-6wt.%Mg alloy has been conducted to explore the relations between slip transmission with fracture behavior. Detailed in-situ electron backscatter diffraction characterization and analysis of 1400 grain boundaries (GBs) were carried out at five different strain states. Three slip transmission parameters, Schmid factor m, Luster-Morris parameter m ′, and residual Burgers vector Δ b, were analyzed to characterize the dislocation-GBs interactions. Both intergranular and intragranular fracture was observed in the tensile test. The intergranular fractures tend to occur at slip-blocked GBs due to local strain concentration. The intragranular fracture traces coincide with grains having GBs where slip transmission traces were observed. The revealed correlations of slip transmission/blockage with fracture can be applied to failure analysis and simulation of polycrystalline materials. Graphical abstract: Image, graphical abstract